2018
DOI: 10.1111/jgs.15459
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of Moderate to Severe Pain among Hospitalized Older Adults

Abstract: Twenty percent of older adults admitted to a general medicine service had moderate to severe pain. Further research about optimal pain management in hospitalized older adults, particularly those with chronic pain, is necessary to improve care in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 51 publications
(98 reference statements)
1
16
1
3
Order By: Relevance
“…Integral to this nursing activity is recognition that the older person's self-report can offer the most accurate and reliable method for identifying and characterising their pain (Herr, 2011). Yet, the Deng et al (2018) study of the prevalence and characteristics of hospitalised older people found up to 20% were suffering from moderate to severe pain. Further, that older patients with pre-existing chronic pain had less reduction in their pain intensity score from admission to discharge when compared to those without chronic pain (Deng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Integral to this nursing activity is recognition that the older person's self-report can offer the most accurate and reliable method for identifying and characterising their pain (Herr, 2011). Yet, the Deng et al (2018) study of the prevalence and characteristics of hospitalised older people found up to 20% were suffering from moderate to severe pain. Further, that older patients with pre-existing chronic pain had less reduction in their pain intensity score from admission to discharge when compared to those without chronic pain (Deng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…() study of the prevalence and characteristics of hospitalised older people found up to 20% were suffering from moderate to severe pain. Further, that older patients with pre‐existing chronic pain had less reduction in their pain intensity score from admission to discharge when compared to those without chronic pain (Deng et al., ). Despite the evidence that this problem exists, there is a lack of knowledge as to why pain care provision for the older person in acute care continues to be less than optimal.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the median self-reported recovery level prior to each APEP session was 6 of 10 points (Table 4), which may indicate insufficient recovery levels in some participants. Pain, sleep disturbances and fatigue are very common conditions in older people, challenging to manage and often inadequately treated [8085]. In a future main study (as has been the case in the current study), intensive and adequate management of pain, sleep disturbances and fatigue within usual care procedures should enable affected study participants to participate in (additional) rehabilitation treatments, such as physiotherapy.…”
Section: Discussionmentioning
confidence: 95%
“…One study reported that between 1999 and 2010, opioid prescriptions for older adult outpatients increased from 4% to 9% . Another examined hospitalised patients aged 65 years and older and found that 51% received opioids before they were admitted and 8 out of 10 patients increased their use of opioids during their hospital stay . In a nationwide study of over 250 000 individuals, the use of prescription opioids was highest among white, educated females between the ages of 70 and 75 .…”
Section: Introductionmentioning
confidence: 99%